2005
DOI: 10.1002/humu.20169
|View full text |Cite
|
Sign up to set email alerts
|

Genomic rearrangements in theBRCA1 andBRCA2 genes

Abstract: Mutations in the BRCA1 and BRCA2 genes predispose women to breast and ovarian cancer. BRCA1 and BRCA2 are 83 and 86 kb long, with coding sequences of 5.7 and 10.2 kb, scattered over 22 and 26 coding exons, respectively. The large majority of the alterations identified in these genes are point mutations and small insertions/deletions. However, an increasing number of large genomic rearrangements are being identified, especially in BRCA1. This review gives a brief overview of the techniques used to screen the BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
126
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 49 publications
10
126
0
6
Order By: Relevance
“…Only one of the studies published thus far analyzed BRCA1 and BRCA2 for large genomic rearrangement mutations, although this type of alteration can be common, particularly in the BRCA1 gene (23). In the current study, one of the 22 BRCA1 mutations (f5%) was a large genomic deletion.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Only one of the studies published thus far analyzed BRCA1 and BRCA2 for large genomic rearrangement mutations, although this type of alteration can be common, particularly in the BRCA1 gene (23). In the current study, one of the 22 BRCA1 mutations (f5%) was a large genomic deletion.…”
Section: Discussionmentioning
confidence: 60%
“…However, several studies have now reported the common occurrence of large, genomic alterations (rearrangements and deletions) in BRCA1 and BRCA2 (21,22). For BRCA1, this type of mutation represents 8% to 40% of all BRCA1 mutations identified in families from the United Kingdom, United States, France, Germany, The Netherlands, and Italy, but may be rare in the Danish population (6,23,24). This suggests that most studies will have underestimated the prevalence of BRCA1 and BRCA2 mutations in ovarian and breast cancer populations.…”
mentioning
confidence: 99%
“…This finding suggests that, in addition to the high density of intragenic alu repeats (2 ) and the upstream BRCA1 pseudogene (11 ), downstream sequences may render the BRCA1 locus particularly prone to rearrangements (in this regard, it is interesting to note that alu repeats are highly frequent in a 35-kb genomic region downstream of BRCA1 exon 24). Second, we detected a considerable proportion of genomic amplifications (3 of 8), whereas most BRCA1 LGRs identified in other populations are deletions (22,23 ).…”
Section: Discussionmentioning
confidence: 74%
“…LGRs (del exon 1-24, dup exon 19 -20, dup exon 20, exon 21-22 amplification, and del exon [23][24]. The molecular characterization of genomic rearrangements is time consuming and technically demanding, especially if genomic amplifications or deletions involve regions outside the BRCA1 locus.…”
Section: Discussionmentioning
confidence: 99%
“…34 The majority of these elements lost their transposition ability a long time ago, although some of them, in particular, LINE-1 and Alu, have been shown to maintain this capacity, thus contributing to recent evolutionary history of the primate genomes 35 and also to the genomic instability found to be involved in cancer and several genetic disorders. 36 Similar to what happens with the BRCA1 gene, often known to suffer Alu-mediated deletions, 37,38 analysis of SPG11 also shows a high density of interspersed repeats, namely Alu elements, which together with the large size of this gene (~101 kb) favors the occurrence of various rearrangements. In addition, and similar to what seems to be happening with the SPG11 deletions, the Alu-mediated BRCA1 rearrangements arise from nonallelic homologous recombination.…”
Section: Evolutionary Conservation Of Alus Involved In Human Spg11 Dementioning
confidence: 82%